Radioembolization in patients with progressive gastrointestinal stromal tumor liver metastases undergoing treatment with tyrosine kinase inhibitors - Rathmann, Nils-Andreas; Diehl, Steffen J.; Dinter, Dietmar; Schönberg, Stefan; Hohenberger, Peter (Journal of vascular and interventional radiology, 2015)
Gastrointestinal stromal tumors (GISTs) spread frequently to the peritoneum and the liver. If metastasectomy or tyrosine kinase inhibitors (TKIs) fail, interventional ablation techniques are considered. The purpose of this study is to assess the progression-free interval (PFI) of GIST liver metastases after radioembolization (RE). Eleven patients with progressive GIST liver metastases undergoing TKI therapy were referred for RE; one was excluded because of a large hepatopulmonary shunt, and one was lost to follow-up. Depending on intrahepatic tumor distribution, one or both liver lobes were treated with RE. Contrast-enhanced magnetic resonance imaging, contrast-enhanced computed tomography (CT), and [18F]fluorodeoxyglucose positron-emission tomography/CT were used for follow-up. In all, 16 liver lobes were treated with a mean activity of 1.06 GBq ± 0.37 (range, 0.55-1.88) per lobe. Three patients showed complete response, five showed partial response, and one showed stable disease. No patient showed progressive disease after RE. Median PFI was 15.9 months (range, 4-29 mo). Median survival was 29.8 months (range, 10-72 mo). No radiation-induced liver disease developed; however, one patient required surgery for persistent stomach ulcer. RE offers a safe and effective treatment for patients with GIST liver metastases who do not show a response to TKIs. RE could be an option for earlier phases of therapy in patients with mutational status. The results might also challenge the notion that GISTs are resistant to radiation therapy.